Broiler Performance, Carcass Characteristics, Haematology and Serum Biochemical Parameters as Affected by Hot Red Pepper (Capsicum frutescens) Powder Supplementation - Shawle, Kassa; Urge, Mengistu; Animut, Getachew; Zeryehun, Tesfaheywet (Indian Journal of Animal Nutrition, 2018)
This study was undertaken to evaluate the effects of hot red pepper (Capsicum frutescens) as feed additive on performance and health parameters of broilers. A total of 192 Cobb-500 day-old broiler chicks were randomly distributed into four treatments with three replicates. Hot red pepper (Hrp) was included in the ration at 0 (0Hrp), 0.75 (0.75Hrp), 1.5 (1.5Hrp) and 2.25% (2.25Hrp) in treatment T1, T2, T3 and T4, respectively. Growth performance, carcass characteristics, hematology and serum biochemical parameters were observed. Average daily weight gain, feed intake and feed conversion ratio were similar in all the treatments. The birds of T3 group had higher (P<0.05) breast, drumstick, thigh, heart and gizzard percentage. Sex differences were significant in slaughter weight, dressed weight and eviscerated, carcass and thigh percentages with greater values for males than females. The blood aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, glucose and triglyceride levels were reduced (P<0.05), whereas total immunoglobulin concentration increased in groups that were supplemented with Hrp. In conclusion, chicken consumed the rations containing Hrp powder but the effects was not reflected on growth performance of broilers. Lowered values of biochemical parameters and increased carcass portions and immunoglobulin concentration with inclusion of Hrp indicated the better health condition of the broilers.